1996
DOI: 10.1083/jcb.132.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Detection of protein kinase activity specifically activated at metaphase-anaphase transition.

Abstract: Abstract. We Z 11:2895-2902). This observation implies a possibility that there is a protein kinase specifically activated at metaphaseanaphase transition. To further analyze the cell cycledependent GFAP phosphorylation, we prepared monoclonal antibodies KT13 and KT34 which recognize the phosphorylation of GFAP at Serl3 and Ser34, respectively. Immunocytochemical studies with KT13 and KT34 revealed that the GFAP phosphorylation in the cleavage furrow during late mitotic phase occurred not only in glioma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…3A, lane 5) (Liao and Omary, 1996). The increase in the association coincident with the timing of S and G2/M phases of the cell cycle, also correlated with IFs hyperphosphorylation (Liao and Omary, 1996;Sekimata et al, 1996). This lends support to our observations with…”
Section: Association Of 14-3-3␥ and Gfap In Astrocytessupporting
confidence: 86%
See 1 more Smart Citation
“…3A, lane 5) (Liao and Omary, 1996). The increase in the association coincident with the timing of S and G2/M phases of the cell cycle, also correlated with IFs hyperphosphorylation (Liao and Omary, 1996;Sekimata et al, 1996). This lends support to our observations with…”
Section: Association Of 14-3-3␥ and Gfap In Astrocytessupporting
confidence: 86%
“…Hyperphosphorylation of IFs is directly correlated with their disassembly into non-filamentous soluble structures (Kawajiri et al, 2003). Under physiological conditions, it is known that GFAP becomes hyperphosphorylated during S and G2/M phases of the cell cycle (Sekimata et al, 1996). To elucidate whether the change in GFAP phosphorylation during the cell cycle would affect its interaction with 14-3-3␥, we synchronized astrocytes in primary cultures at G1/S stages of the cell cycle by aphidicolin treatment (Liao and Omary, 1996), and carried out coimmunoprecipitation assays.…”
Section: Association Of 14-3-3␥ and Gfap In Astrocytesmentioning
confidence: 99%
“…Less is known about the sites and kinases involved in GFAP phosphorylation in intact cell systems, but a start has been made. Japanese workers used monoclonal antibodies recognizing specific phosphorylation sites and immunofluorescence to demonstrate that one threonine and three serines in the head region of GFAP are phosphorylated in vivo at different stages of the cell cycle (56)(57)(58). With regard to the kinases responsible for these in vivo phosphorylations, present evidence points to the direct or indirect participation of PKA, CaMK II, the cdc-2 kinase and an unknown kinase (CF kinase) (58).…”
Section: General and Functional Aspects Of Gfap Phosphorylationmentioning
confidence: 99%
“…Phosphorylation of disassembled subunits inhibits their assembly into filaments (47,61), with subunit exchange in the case of GFAP being suppressed in proportion to the extent of phosphorylation (62). Moreover, IF protein phosphorylation plays a crucial role in dividing cells, where evidence from cell cultures has shown that the disassembly of the cytoskeleton preceding mitosis in some cells is regulated by a site-specific increase in the phosphorylation state of vimentin and GFAP (57,(63)(64)(65). In interphase cells changes in the phosphorylation state of IF proteins may have profound effects on the structure of the cytoskeleton, as shown by studies in which hyperphosphorylation of vimentin induced by protein phosphatase inhibitors (66,67) or the antitumor drug fostriecin (68) was associated with intermediate filament reorganization.…”
Section: General and Functional Aspects Of Gfap Phosphorylationmentioning
confidence: 99%
“…These six amino acid residues are highly conserved among species, implying the biological importance of GFAP phosphorylation [7]. Enzymes including protein kinase A (PKA), protein kinase C (PKC), calcium/calmodulin dependent protein kinase II (CaMKII), Rho kinase, cleavage furrow (CF) kinase and Cdc2 kinase modulate the phosphorylation of one or more of the GFAP residues [8][9][10][11][12]. Phosphorylation in the N-terminal region (head domain) affects GFAP assembly and in the C-terminal region (tail domain), phosphorylation of Ser-389 affects interactions between GFAP and other intermediate filaments or proteins [10].…”
Section: Introductionmentioning
confidence: 99%